QUANTITATIVE DETERMINATION OF ASENAPINE MALEATE USING REVERSE PHASE-HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - T.R.PARTHASARATHI,; TAMIL SELVI SRINIVAS,; M.VANITHA SRI,; SEGU SAI RAM,; MULLA MAHABOOB BASHA,; PUDI RAJESH., (International Journal of Pharma and Bio Sciences, 2012)
A novel isocratic reverse-phase high performance liquid-chromatography method for determination of asenapine maleate was developed and validated after optimization of various chromatographic conditions. Samples were separated on a waters x-terra C18 (100 mm × 4.6 mm, 3.5 μ) analytical column. The mobile phase used was acetonitrile: 0.1M phosphate buffer (pH 3.2) 65:35%v/v operated at 30 °C column oven temperature was pumped at a flow rate of 1.0 mL min−1 and the column eluents were monitored at a wavelength of 272 nm. When sample was injected into the Finnigan surveyor high performance liquid-chromatography system through Finnigan surveyor auto-sampler injector, separation was achieved within 5.0 min. The present method was demonstrated and it was validated with the acceptable values for selectivity, linearity (within the expected concentration range (10–50 μg mL−1; r2 > 0.999)), recovery (>95%), precision (%RSD < 2.0), sensitivity (limit of detection: 1.85 µg mL−1 and lower limit of quantification: 2.34 µg mL−1), robustness, and ruggedness.